Answer:
(g - f)(x) = 3x - 33
Step-by-step explanation:
Arrange f(x)= 2x + 13 and g(x) = 5x -20 vertically as shown below:
g(x) = 5x - 20
-f(x) = -2x - 13
----------------------
(g - f)(x) = 3x - 33
4(2x + 10)=0
8x + 40 = 0
8x = -40
x = -5
A fraction x/y is a ratio between two numbers x and y.
The ratio is preserved if both x and y are scaled up or down by the same number n.
This means you can obtain any fraction equivalent to x/y by multiplying both x and y by n, i.e. (n*x)/(n*y).
Then we have 1/4 = (2*1)/(2*4) = 2/8, for example.